2019
DOI: 10.1016/j.athoracsur.2019.03.080
|View full text |Cite
|
Sign up to set email alerts
|

Stability After Initial Decline in Coronary Revascularization Rates in the United States

Abstract: Background. It remains uncertain how advances in revascularization techniques, availability of new evidence, and updated guidelines have influenced the annual rates of coronary revascularization in the United States.Methods. We used the Nationwide Inpatient Sample data from 2005 to 2014 with appropriate weighting to determine national procedural volumes. To present accurately overall percutaneous coronary intervention (PCI) rates, PCI with same-day discharge numbers per year were estimated from the available l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 11 publications
1
16
0
Order By: Relevance
“…Several studies [4][5][6]9,11,14,23 have found a decrease in coronary revascularization procedures in the United States in the past 2 decades. However, most of these studies [4][5][6]9,11,14,23 were not contemporaneous, included only certain subsets of patients (eg, patients with Medicare insurance or AMI), or examined trends of surgical or percutaneous revascularization procedures. Although our primary objective was to assess the temporal changes among hospital inpatient risk profiles, procedural characteristics, and procedural mortality, the current study, to our knowledge, provides the most up-to-date nationwide analysis of the annual trends in coronary interventions conducted in hospitals.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies [4][5][6]9,11,14,23 have found a decrease in coronary revascularization procedures in the United States in the past 2 decades. However, most of these studies [4][5][6]9,11,14,23 were not contemporaneous, included only certain subsets of patients (eg, patients with Medicare insurance or AMI), or examined trends of surgical or percutaneous revascularization procedures. Although our primary objective was to assess the temporal changes among hospital inpatient risk profiles, procedural characteristics, and procedural mortality, the current study, to our knowledge, provides the most up-to-date nationwide analysis of the annual trends in coronary interventions conducted in hospitals.…”
Section: Resultsmentioning
confidence: 99%
“…However, the annual volumes of both PCI and CABG decreased significantly in more recent years possibly because of advances in medical therapy, the emergence of data questioning the benefit of PCI in stable CAD, and the increasing implementation of appropriate use criteria. [8][9][10][11] Whether these temporal changes in procedural volume were associated with changes in the risk profiles of patients referred for percutaneous or surgical coronary revascularization and the outcomes of these procedures remain unknown. This study used a nationwide, representative sample hospital inpatients in the United States to assess the temporal changes in baseline characteristics of patients undergoing PCI or CABG and crude and risk-adjusted in-hospital mortality after PCI or CABG stratified by clinical indication.…”
Section: Introductionmentioning
confidence: 99%
“…18 A contraction in surgical revascularization volume is a natural consequence of the increase in percutaneous procedures, as already discussed elsewhere. 19,20 Valve surgery volume, in contrast, remained steady in NTH (−5.26%)…”
Section: The Impact Of the 2011 Duty-hour Regulations On Outcomementioning
confidence: 99%
“…Patients who currently present for CABG have more comorbidities and a higher percentage have had percutaneous intervention than in prior years. 45 , 46 , 47 LaPar and colleagues 48 suggest that an expected isolated CABG mortality of less than 1% can be achieved in only 60% of patients. We propose that surgeon specialization in coronary surgery of women should be considered because surgeons are treating sicker patients while at the same time being faced with mandated transparency, intense scrutiny, and public reporting of outcomes.…”
Section: Optimization Of Outcomes: the Futurementioning
confidence: 99%